TANTANGAN IMPLEMENTASI TEKNOLOGI INFORMASI DALAM PENYELESAIAN SENGKETA PASAR MODAL OLEH BADAN ARBITRASE PASAR MODAL INDONESIA (BAPMI) - Kusumaningsih, Tessa (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study examines the challenges of implementing information technology in the resolution of capital market disputes by BAPMI, an institution established in 2002 to resolve civil disputes in the capital market through out-of-court mechanisms. The study identifies various significant obstacles in the adoption of information technology, including limitations in digital infrastructure, a lack of understanding among stakeholders of the online arbitration system, resistance to change from conventional methods, as well as security and confidentiality challenges in the digital process. The analysis results show that although information technology has great potential to enhance the efficiency and effectiveness of dispute resolution through process automation, increased accessibility, and expedited resolution times, its implementation requires a comprehensive strategy that includes infrastructure development, human resource training, and regulatory harmonization. This research provides strategic recommendations for the digital transformation of BAPMI that can enhance investor confidence and strengthen the Indonesian capital market ecosystem